Advances in dairy ingredients - Augustin, M. A.; Smithers, Geoffrey W. (IFT Press series, 2013)
Functional foods are emerging as key drivers of the global food economy and dairy ingredients and technology are at the forefront in these developments. Advances in Dairy Ingredients provides an international perspective on recent developments in the area of dairy ingredients and dairy technology